2014
DOI: 10.1016/s2213-8587(14)70034-8
|View full text |Cite
|
Sign up to set email alerts
|

Age-related and disease-related muscle loss: the effect of diabetes, obesity, and other diseases

Abstract: The term sarcopenia refers to the loss of muscle mass that occurs with ageing. On the basis of study results showing that muscle mass is only moderately related to functional outcomes, international working groups have proposed that loss of muscle strength or physical function should also be included in the definition. Irrespective of how sarcopenia is defined, both low muscle mass and poor muscle strength are clearly highly prevalent and important risk factors for disability and potentially mortality in indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
664
0
21

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 861 publications
(706 citation statements)
references
References 139 publications
(152 reference statements)
21
664
0
21
Order By: Relevance
“…Moreover, data supporting improvements in weight loss treatment of obese older adults are limited (Mathus-Vliegen 2012). Studies on rodents showed that muscle mass repair mechanisms, such as activation of a quiescent population of myogenic cells, is dysfunctional in older individuals (Kalyani et al 2014;Tidball 2011). It has been suggested that defects in repair mechanisms are related to the tendency of ageing satellite cells to achieve an Badipocytic^phenotype (Kalyani et al 2014).…”
Section: Lean Mass Decreasementioning
confidence: 99%
“…Moreover, data supporting improvements in weight loss treatment of obese older adults are limited (Mathus-Vliegen 2012). Studies on rodents showed that muscle mass repair mechanisms, such as activation of a quiescent population of myogenic cells, is dysfunctional in older individuals (Kalyani et al 2014;Tidball 2011). It has been suggested that defects in repair mechanisms are related to the tendency of ageing satellite cells to achieve an Badipocytic^phenotype (Kalyani et al 2014).…”
Section: Lean Mass Decreasementioning
confidence: 99%
“…In young individuals, excess weight is associated with increased muscle mass and strength, probably due to musculoskeletal adaptations due to increased overload 19 . The aging process, however, compromises this adaptive mechanism, so that excess adiposity leads to a decrease in muscle strength and increases the risk of physical disability in this population 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Muscle fat infiltration may also mediate this relationship 20 . Actually, it was previously observed that the performance of elderly women in the sit-up test had a negative correlation with BMI and also with other body fat indexes 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Factors relating to skeletal muscle mass and strength changes include the loss of motor units innervating muscle, age-related hormone changes, muscle hypoxia resulting from atherosclerosis and chronic proinflammatory status, decreased physical activity and protein intake, age-related insulin resistance, and mitochondrial dysfunction [23]. Aging leads to a preferential reduction of type II myofiber size.…”
Section: Aging Promotes Sarcopenia and Frailtymentioning
confidence: 99%